Risk Analyses Factor of Infant Mortality Caused by Tetanus Neonatorum in East Java - Selvy Novita Sari (Universitas Airlangga, 2017)
Tetanus neonatorum (TN) is an infection in infants <28 days old caused by the bacterium Clostridium tetani which enter the body through wounds. TN is one of the causes of neonatal death in the world. TN Cases are found in 14 provinces in Indonesia, East Java has the second-highest TN case in Indonesia. The purpose of this study was to analyze the relationship between maternal tetanus toxoid (TT) immunization status, parity level, TN rescue rate, and umbilical cord care with death in infants with TN. This study was an observational analytic study with a cross-sectional design using 59 respondents obtained from the T2 report to the East Java Provincial Health Office in 2014-2016. Data analysis using the Chi-square test. The results showed that TT immunization status of pregnant women (p = 0.257), maternal parity level (p = 0.034; PR = 0.39; 95% CI 0.16-0.98), TN rescue rate (p = 0.061), and cord care (p = 0.007; PR = 2.31; 95% CI 1.29-4.15). The conclusion of this study is that there is a relationship between maternal parity level and umbilical cord care with death in infants with TN, and there is no relationship between maternal TT immunization status and the TN rescue rate with death in infants with TN in East Java in 2014-2016. Research suggestions, efforts that need to be done to reduce the risk of infant death are counseling related to TT immunization for pregnant women, regulating pregnancy, giving birth, and clean cord care.